Lowering fluoroscopy pulse rates to reduce radiation dose during cardiac procedures. Issue 4 (2nd December 2018) - Crowhurst, James; Whitby, Mark
Abstract : Radiation dose to patients undergoing cardiac imaging procedures in cardiac catheterisation laboratories (cath labs) can be relatively high, so implementing strategies to reduce dose is important. Lowering the fluoroscopy pulse rate is a simple, yet effective method to reduce radiation dose. Sensible, iterative changes made in this area have the potential for significant patient and staff radiation dose reduction.